Factors Influencing Future Anxiety among Teachers in Southwest, Nigeria - Nwakaego Obi, Sabina; Olawoyin, Eniola Keji (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
Teachers in Nigeria increasingly face economic uncertainty, social instability, and occupational stress, conditions that contribute to heightened anxiety about the future. While research has highlighted the prevalence of mental health challenges among teachers, limited attention has been given to the developmental and psychological factors shaping such anxieties. This study examined the joint and relative influence of childhood experiences, psychological mindedness, and resilience on future anxiety among public junior secondary school teachers in Southwest Nigeria. A descriptive survey design was employed, involving a sample of 2,000 teachers drawn through multi-stage sampling across three states. Data were collected using validated instruments, including modified versions of the Future Anxiety Scale, Psychological Mindedness Scale, Connor-Davidson Resilience Scale, and scales measuring adverse and benevolent childhood experiences. The data were analysed using multiple regression at a 0.05 level of significance. Findings revealed that childhood experiences, psychological mindedness, and resilience jointly accounted for the variance in future anxiety, indicating a substantial predictive influence. Childhood experiences emerged as the strongest predictor, followed by resilience and psychological mindedness. These results suggest that teachers’ anxiety about the future is shaped not only by current socio-economic pressures but also by the enduring impact of early life experiences and their capacity to engage in adaptive coping. The study concludes that interventions aimed at strengthening resilience and fostering psychological mindedness, alongside trauma-informed support, are crucial for enhancing teachers’ well-being and reducing anxiety.